Identification of Emotional and Behavioral Disorders among First Grade Students: Identifikasi Gangguan Emosional dan Perilaku pada Siswa Kelas Satu - Aisyah, Nur; Mahabbati, Aini (Indonesian Journal of Innovation Studies, 2025)
General Background: Emotional and behavioral disorders (EBD) among elementary school children are often misinterpreted as normal developmental phases, leading to delayed interventions. Specific Background: In rural schools, such as SD Negeri Teluk Pandan, teachers face difficulties in recognizing EBD due to limited training, lack of systematic tools, and minimal parental collaboration. Knowledge Gap: Few studies have explored early identification of EBD in lower-grade elementary settings in Indonesia, particularly in underserved regions. Aims: This study aims to identify the forms, characteristics, and influencing factors of EBD in first-grade students, as well as strategies used by teachers and parents in the identification process. Results: Findings reveal two main categories of EBD: internalizing behaviors (withdrawal, passivity, excessive anxiety) and externalizing behaviors (aggression, yelling, hyperactivity). These behaviors disrupted classroom learning and were influenced by family dynamics, school environment, and individual emotional regulation. Teachers and parents employed ad-hoc strategies, including personal approaches, flexible classroom management, and limited home-based interventions. Novelty: The study highlights the absence of systematic identification methods and emphasizes the importance of collaborative, context-specific approaches between teachers and parents. Implications: Early structured identification programs, teacher training, and cross-sector collaboration are recommended to create inclusive and supportive learning environments for children with EBD.Highlight : Early identification helps detect emotional and behavioral disorders in students. Teachers and parents must collaborate intensively for effective intervention. Inclusive learning environments require structured teacher training. Keywords : Emotional And Behavioral Disorders, Identification, Elementary School, Case Study, Early Intervention